Reliability of Buried Pipes in Heterogeneous Soil Subjected to Seismic Loads - Benzeguir, H.; Elachachi, S. M.; Nedjar, D.; Bensafi, M. (Engineering, Technology & Applied Science Research, 2021)
Dysfunctions and failures of buried pipe networks, like sewer networks, are studied in this paper from the point of view of structural reliability and heterogeneity of geotechnical conditions in the longitudinal direction. Combined soil spatial variability and Peak Ground Acceleration (PGA) induce stresses and displacements. A model has been developed within the frame of geostatistics and a mechanical description of the soil–structure interaction of a set of buried pipes with connections resting on the soil by a two-parameter model (Pasternak model). Structural reliability analysis is performed considering two limit states: Serviceability Limit State (SLS), related to large "counter slope" in a given pipe, and Ultimate Limit State (ULS), corresponding to bending moment.